Modern Technologies and Applications of ICT in the Training Process of Teachers-Philologists - Shkvorchenko, N. M.; Berkeshchuk, I. S.; Shcherbak, I. V.; Masytska, T. E.; Chornyi, I. V. (My University, 2020)
he use of online technology of an experimental, gaming, competitive nature helps unite the virtual context and the acquisition of analytical skills in an environment, where personal communication is impossible, and the learning process requires high-quality preparation and understanding of the level of acquisition of speech skills. Studies show that within the conditions of distance learning of language and literature teachers (philologists), special difficulties are caused by the study of new technologies related to speech practice, stylistics, text creation; the reason for this is the insufficient number of group and heuristic activities, work in pairs, lack of sufficient speech practice of high communicative and intellectual level. Online quizzes as a technology of competition, games aims to increase the register, level and intensity of communication; they can potentially overcome the lack of authentic communication and academic traditions in the training of philologists. The purpose of this study is to show the prospects for the use of modern information and computer technologies. Intensive informatization of the educational process has its own organizational specifics: the willingness and availability of technical capabilities not only for students - philologists, but also for the teaching staff of universities and administrations. The condition for successful informatization is the ability of teachers to effectively use all available potential. The study focuses on the use and scope, difficulties in implementing information and communication technologies, and separate competitive interactive forms in higher education of language and literature teachers in terms of distance education.
Shkvorchenko N. M. Modern Technologies and Applications of ICT in the Training Process of Teachers-Philologists / N. M. Shkvorchenko, I. S. Berkeshchuk, I. V. Shcherbak, T. E. Masytska, I. V. Chornyi // International Journal of Higher Education. – 2020. – Vol. 9, № 7. – P. 84-93.
Keywords: informatization of educational process; communication technologies; pedagogical education; online quizzes; open education